2020
DOI: 10.1016/j.rmcr.2020.101189
|View full text |Cite
|
Sign up to set email alerts
|

Influences of bovine colostrum on nasal swab microbiome and viral upper respiratory tract infections – A case report

Abstract: Bovine colostrum has been advocated as a source of immunity against external environmental microorganisms. Recurrent upper respiratory tract infections present a critical public health concern in the developing countries. The present case report was performed to assess the influence of bovine colostrum in preventing recurrent upper respiratory tract infections caused by respiratory viruses in an adult in Jordan in addition to its effect on respiratory microbiome. In conclusion, bovine colostrum was successful … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…HRV detection was performed according to a recent publication. 29 The absolute quantification / second derivative maximum strategy was used to analyze the samples. A positive result was registered for C t values less than or equal to 40 cycles, while a negative result was registered in the absence of a C t value and for C t values were greater than 40 cycles.…”
Section: Clinical Samples and Detection Of Sars-cov-2 And Hrvmentioning
confidence: 99%
“…HRV detection was performed according to a recent publication. 29 The absolute quantification / second derivative maximum strategy was used to analyze the samples. A positive result was registered for C t values less than or equal to 40 cycles, while a negative result was registered in the absence of a C t value and for C t values were greater than 40 cycles.…”
Section: Clinical Samples and Detection Of Sars-cov-2 And Hrvmentioning
confidence: 99%
“…A case study presented by Alsayed et al [ 29 ] showed the effectiveness of BC in preventing upper respiratory tract infection (URTI) and nasal swab microbiome caused by respiratory viruses in an adult. This study was conducted on a 27-year-old patient who was a nonsmoker and nonalcoholic and took a healthy diet with supplementation in three periods: period a, 1 g of bovine colostrum (two capsules, each 500 mg) for 4 weeks; period b, 2 weeks after the end of the period a, 1 g BC at dawn for 3 days; period c, after period b, supplemented with 1 g BC at dawn 2 times/week for 4 weeks.…”
Section: Current Evidence Of Therapeutic Use Of Bcmentioning
confidence: 99%
“…Recently, the approaches of exploring BC-based feed for feeding fish [ 26 ], broiler chickens [ 27 ], and birds [ 28 ] have been reported in the literature, and it has been demonstrated to be successful in delivering a suitable high protein content for overall body composition. Scientific evidence from placebo-controlled clinical trials indicates that BC components have a wide range of pharmacological uses in the prevention and pretreatment of acute and chronic diseases [ 29 , 30 ]. Figure 1 depicts an outline of the elements of bovine colostrum, as well as their health and industrial uses.…”
Section: Introductionmentioning
confidence: 99%
“…Saad et al [30] have reported that colostrum has both antimicrobial and endotoxinneutralizing effects. Thus, it can be effective in the prophylaxis of recurrent upper respiratory tract infections and diarrhea [30,31]. The consumption of bovine colostrum can also lead to changes in the respiratory microbiome, which was shown by nasal swab samples [31].…”
Section: Bioactive Components In Colostrum 21 Bioactive Compoundsmentioning
confidence: 99%